INTERPRETING CONTINUOUS GLUCOSE MONITORING DATA IN NON-DIABETIC INDONESIANS: A PHENOMENOLOGICAL STUDY OF MEANING-MAKING AND LIFESTYLE DECISIONS - Yulia Yulia; Wendy Abigail; Thurayya Abdulwahid Eid; Masfuri Masfuri (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2026)
The rising prevalence of type 2 diabetes highlights the need for early metabolic awareness strategies. Continuous glucose monitoring (CGM), originally developed for diabetes management, is increasingly used by non-diabetic individuals seeking personalized health insights. However, evidence remains limited regarding how users interpret CGM data and apply it to lifestyle decisions, particularly in low- and middle-income countries Objective: This study explored the experiences of non-diabetic adults in Indonesia using CGM. Method: This phenomenological study involved six adults with CGM experience. Data were collected through HBM-informed interviews and analyzed using directed qualitative content analysis combining deductive and inductive approaches. Results: Four themes emerged: (1) emotional and cognitive sense-making of glucose visibility; (2) CGM as a reflective learning and validation tool; (3) personal and social context shaping meaning; and (4) navigating structural and contextual constraints.  Discussion:  The CGM use among non-diabetic Indonesian individuals generated complex emotional, cognitive, social, and cultural responses that shaped how glucose data were interpreted and translated into lifestyle behaviors.  CGM enhanced metabolic awareness and motivated preventive actions; however, anxiety related to glucose fluctuations, limited healthcare guidance, device reliability issues, and sociocultural barriers influenced the sustainability and meaning of its use.  Conclusion: CGM shapes how individuals perceive and respond to metabolic signals. Findings highlight the need for education, culturally responsive guidance, and CGM integration into preventive care. Nurses play an important role in supporting accurate interpretation and reducing anxiety. Policy efforts should support regulatory guidance, standardized education, and safe CGM integration into preventive and digital health systems.Keywords: continuous glucose monitoring, health promotion, lifestyle behavior, non-diabetic population prevention